Learning from victims’ family narratives: the impact of offline and online harm in cases of intimate partner homicide - Kennedy, Morag C. (Routledge studies in crime and society, 2026)
"Offering a new perspective on intimate partner abuse and homicide, this book recognises the families of victims as legitimate agents of knowledge in terms of the harm experienced by their family members, and considers how this harm is extended to the families themselves. Examining harm from both an offline and online point of view, the book explains the multipurpose roles of offline and online harm and how these roles do not occur in isolation in terms of the victims' and families' abusive experiences. In doing so, it demonstrates the range of harm experienced in the context of intimate partner abuse and homicide, and outlines the overlapping nature of offline and online harm without prioritising one form of harm over the other. Instead, considering the harm experienced as a continuum. Providing theoretical and empirical contributions that are largely absent from existing victimology and harm literature, Learning from Victims' Family Narratives: The Impact of Offline and Online Harm in Cases of Intimate Partner Homicide will be of interest to scholars, researchers, students and practitioners exploring the modern conceptualisation of harm and its impact of individuals beyond the victim and perpetrator"--